Ab initio calculations as a quantitative tool in the inelastic neutron scattering study of a single-molecule magnet analogue. Issue 10 (21st December 2015) - Vonci, Michele; Giansiracusa, Marcus J.; Gable, Robert W.; Van den Heuvel, Willem; Latham, Kay; Moubaraki, Boujemaa; Murray, Keith S.; Yu, Dehong; Mole, Richard A.; Soncini, Alessandro; Boskovic, Colette
Abstract : Ab initio calculations of the electronic structure of Na9 [Tb(W5 O18 )2 ] have allowed interpretation of the inelastic neutron scattering spectra, revealing the subtle relationship between molecular geometry and magnetic properties of two isostructural species. Abstract : Ab initio calculations carried out on the Tb analogue of the single-molecule magnet family Na9 [Ln(W5 O18 )2 ] (Ln = Nd, Gd, Ho and Er) have allowed interpretation of the inelastic neutron scattering spectra. The combined experimental and theoretical approach sheds new light on the sensitivity of the electronic structure of the Tb(iii ) ground and excited states to small structural distortions from axial symmetry, thus revealing the subtle relationship between molecular geometry and magnetic properties of the two isostructural species that comprise the sample.